Potassium channels in human umbilical artery cells - Milesi, María Verónica (2003)
To identify K+ channels of smooth muscle of human umbilical artery using the patch-clamp technique and to study their effect on resting tone of umbilical artery rings. Whole-cell and single-channel patch-clamp recordings in enzymatically isolated smooth muscle cells were made. Measurements of developed isometric force were performed on intact tissue. Delayed rectifier K+ channels (KDR) and large-conductance Ca2+-activated K+ channels (BKCa) contribute to the whole-cell voltage-and time-dependent outward K+ current, as it was specifically inhibited by 5 mM 4-aminopyridine (4-AP; KDR blocker) (92 ± 4% at 0 mV, n = 7), by 1 mM tetraethylammonium (TEA; BKCa blocker) (71 ± 4% at +60 mV, n = 4), and by 200 nM iberiotoxin (BKCa blocker) (64 ± 7% at +60 mV, n = 4). In outside-out patches, BKCa channels had ā single-channel conductance of 132 ± 4 pS (n = 24) in asymmetric K+ conditions and 216 ± 4 pS (n = 4) in a symmetric K+ gradient. The activity of the BKCa channels was significantly augmented by 1 μM Ca2+ in the inside-out configuration. 4-AP had no effect on resting tone of intact arterial rings. TEA produced contraction of arterial rings whereas phloretin, an activator of BKCa, relaxed them, which means that BKCa channels are functional in intact tissue and are involved in the maintenance of resting tone in this human vessel. The identities of K+ channels in the human umbilical artery were shown using the patch-clamp technique, and the physiologic effect of K+ channels on resting tone was documented.